2021
DOI: 10.1029/2021ja029449
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Middle Thermosphere (∼160 km) Composition to the November 20 and 21, 2003 Superstorm

Abstract: The response of thermospheric composition to geomagnetic storms has been studied for several decades. The first such study was carried out by Seaton (1956), who proposed that an increase in molecular oxygen (O 2 ) number density might account for the decrease of electron density during a major storm that took place on January 25, 194925, . Jacchia (1959 first presented evidence of thermospheric density increases during storms using the measured changes in satellite orbital elements, which were explained in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 45 publications
1
44
0
Order By: Relevance
“…TIE‐GCM calculates the major species (O, O 2 , and N 2 ) using vertical molecular diffusion, vertical eddy diffusion, horizontal and vertical advection as well as production and loss due to chemical reactions (Cai et al., 2021; Qian et al., 2014; Sutton et al., 2015; Yu et al., 2021). The O + density is calculated according to the continuity equation considering transport due to neutral winds, transport due to ambipolar diffusion, E × B transport as well as production Q and loss L due to chemical reactions (Liu et al., 2016) ntQ+Ln=()nvi. $\frac{\partial n}{\partial t}-Q+L\cdot n=-\nabla \left(n\cdot {\mathbf{v}}_{i}\right).$ The ion velocity v i combines the different transport processes in Equation .…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…TIE‐GCM calculates the major species (O, O 2 , and N 2 ) using vertical molecular diffusion, vertical eddy diffusion, horizontal and vertical advection as well as production and loss due to chemical reactions (Cai et al., 2021; Qian et al., 2014; Sutton et al., 2015; Yu et al., 2021). The O + density is calculated according to the continuity equation considering transport due to neutral winds, transport due to ambipolar diffusion, E × B transport as well as production Q and loss L due to chemical reactions (Liu et al., 2016) ntQ+Ln=()nvi. $\frac{\partial n}{\partial t}-Q+L\cdot n=-\nabla \left(n\cdot {\mathbf{v}}_{i}\right).$ The ion velocity v i combines the different transport processes in Equation .…”
Section: Datamentioning
confidence: 99%
“…The strong shift of the 27-day signature for O and O 2 at low heights, which is also observed in Figure 7, reflects the role of ionization and recombination on the delayed ionospheric response (Ren et al, 2018) and reveals to which extent the photodissociation has to be considered. The 𝐴𝐴 Ψ𝑁𝑁 2 profiles are estimated according to the implementation (Yu et al, 2021) as…”
Section: The Transition Region Betweenmentioning
confidence: 99%
See 1 more Smart Citation
“…The electric field is not the only source of extreme increase in the electron density. The important role of thermospheric composition changes was demonstrated by Yu et al [5]. Their study showed that the increase in the oxygen mass density reached up to ~90% during the 20-21 November 2003 superstorm.…”
Section: Introductionmentioning
confidence: 90%
“…In this paper, we take an unconventional approach to the study of extreme ionospheric events. Instead of investigating ionospheric responses to extreme space weather events (as is usual for case studies [1][2][3][5][6][7][8][9][10][11][12] or statistical investigations [15][16][17]), we collect statistics of extreme ionospheric disturbances from datasets of two ionosondes. Similar to our study, the extreme values of TEC over Japan with frequencies of once per year, 10 years, and 100 years were investigated using 22-year GPS TEC measurements and 62-year ionosonde slab thickness observations [18].…”
Section: Introductionmentioning
confidence: 99%